2010
DOI: 10.1007/s00449-010-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine alkaline protease from Bacillus altitudinis GVC11 and its application as a dehairing agent

Abstract: A serine alkaline protease from a newly isolated alkaliphilic Bacillus altitudinis GVC11 was purified and characterized. The enzyme was purified to homogeneity by acetone precipitation, DEAE-cellulose anion exchange chromatography with 7.03-fold increase in specific activity and 15.25% recovery. The molecular weight of alkaline protease was estimated to be 28 kDa by SDS PAGE and activity was further assessed by zymogram analysis. The enzyme was highly active over a wide range of pH 8.5 to 12.5 with an optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…Preliminary experiments were set up to standardize the optimal conditions for the enzymatic depilation of goat hides by the rSAPB protease preparation using the dip method. The optimal conditions obtained were 2,000 U enzyme in water float (100% w/v) for 8 h. The process time obtained in this study was shorter when compared to previous results in the literature where the enzymatic dehairing process was fulfilled in time intervals ranging from 18 to 21 h for different animal skins [29] , [30] , [31] , [32] . Experiments were then set up to investigate enzymatic depilation at a semi-industrial scale.…”
Section: Resultsmentioning
confidence: 51%
“…Preliminary experiments were set up to standardize the optimal conditions for the enzymatic depilation of goat hides by the rSAPB protease preparation using the dip method. The optimal conditions obtained were 2,000 U enzyme in water float (100% w/v) for 8 h. The process time obtained in this study was shorter when compared to previous results in the literature where the enzymatic dehairing process was fulfilled in time intervals ranging from 18 to 21 h for different animal skins [29] , [30] , [31] , [32] . Experiments were then set up to investigate enzymatic depilation at a semi-industrial scale.…”
Section: Resultsmentioning
confidence: 51%
“…Interestingly, hair loss was observed in the skin over the infected SGM. The relationship between hair loss and infection was assumed that alkaline protease secreted by MRSA provokes a dehairing at the infection area [27], [28]. It was suggested that a macroscopic dehairing lesion reveals the occurrence of infection in the SGM.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is crucial in enzymatic dehairing of hide in leather industries. The enzyme may have an impending application as a dehairing agent (Vijay Kumar et al, 2011). The result of blood destaining with theprotease in 2 h supports the impending ecofriendly application (Rao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%